The establishment of a 3D anatomical coordinate system for defining vaginal axis and spatial position. (September 2021) - Sinex, Deanna C.E.; Bowen, Shaniel T.; Kashkoush, Ahmed; Rosemond, Arianna; Carter, Danielle; Menon, Prahlad G.; Moalli, Pamela A.; Abramowitch, Steven D.
Highlights: The etiology of pelvic organ prolapse (POP) is poorly understood. The proposed 3D pelvic coordinate system (PCS) allows quantitative analysis of POP. This 3D PCS is robust to patient misalignment and rotation in the MRI scanner. This also presents a novel way to quantify vaginal shape and position in 3D space. The combined methods allow for a more comprehensive study of female pelvic anatomy. Abstract: Background and Objective: Pelvic organ prolapse (POP), the herniation of the pelvic organs toward the vaginal opening, is a common pelvic floor disorder (PFD) whose etiology is poorly understood. Traditional methods for evaluating POP are often constrained to external vaginal examination, limited to 2D, or have poor reproducibility. We propose a reliable 3D anatomic coordinate system for standardized 3D assessment of pelvic anatomy using magnetic resonance imaging (MRI). Methods: The novel 3D anatomic reference system is based on six bony landmarks of the pelvis manually identified in MRI: the ischial spines and the superior and inferior pubic points of the left and right pubic symphysis. The origin of this system is defined as the midpoint of the ischial spines. The reproducibility and applicability of the pelvic coordinate system were evaluated by (1) implementing it in a new method to quantify vaginal position and axis (angulation) in 3D space from MRI segmentations of the vagina and (2) computing the intraclass correlation (ICC) on coordinate system and vaginal measures. The MRI analysis was performed by four non-medically trained observers on five pelvic MRI datasets on approximately five separate occasions. Results: Overall, all bony landmarks had excellent intra-observer reliability and inter-observer reliability (ICC>0.90); intra-observer reliability was moderate-to-good among the vaginal position parameters (0.5<ICC≤0.90) and moderate for the vaginal axis angles (0.50<ICC≤0.75); inter-observer reliability was moderate in the vaginal position coordinates and vaginal axis measures. On average, within-observer differences in the vaginal position and angle measures relative to the overall mean were <1 mm and <1°, respectively. Conclusions: The proposed anatomic coordinate system and vaginal analysis approach allow quantitative assessment of pelvic anatomy that is robust to the experience level of the observer. The application of these methods in radiographic studies will give new insight into the underlying anatomic changes involved in the pathogenesis of POP and other PFDs and help better understand their etiology.